(untitled) (Herald of Journalism, 2016)
The author discusses the current issue of the reform of the market. In our time – this is important because the mass media is in need of transformation in accordance with the state program “Strategy” Kazakhstan – 2050 “and the political, economic developments in Kazakhstan. Media in the modern world is changing and becoming more commercial and independent of the state system of globalization and integration of the mass media.